2013
DOI: 10.1007/s00246-013-0745-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Early-Onset Chronic Progressive Anthracycline Cardiotoxicity in Children: Different Response Patterns of Right and Left Ventricles

Abstract: We aimed to assess early-onset chronic progressive cardiotoxicity in the left and right ventricles with increasing cumulative anthracycline doses. We evaluated 72 patients within the first year after doxorubicin and/or daunorubicin treatment (median 1.3 months; range 0.3-11.5) and 31 healthy controls. Pretreatment and posttreatment QT interval analyzes were performed in 27 newly diagnosed patients. The echocardiographic data of all examinations of 72 patients were classified into three groups according to inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 36 publications
5
21
0
1
Order By: Relevance
“…They also found that the tricuspid annular peak systolic velocity (S 0 ) was significantly lower in a patient group receiving anthracycline at doses[240 mg/m 2 than those observed in a control group. In accordance with the findings of Kocabas et al [2], the impairment of RV and LV function after anthracycline treatment using cardiac magnetic resonance imaging has also been described in long-term survivors of childhood cancer [4]. For the convenience of the readership of Pediatric Cardiology, we add that recently our group published normal S 0 values with z-scores for healthy pediatric patients [3].…”
Section: To the Editorsupporting
confidence: 85%
See 3 more Smart Citations
“…They also found that the tricuspid annular peak systolic velocity (S 0 ) was significantly lower in a patient group receiving anthracycline at doses[240 mg/m 2 than those observed in a control group. In accordance with the findings of Kocabas et al [2], the impairment of RV and LV function after anthracycline treatment using cardiac magnetic resonance imaging has also been described in long-term survivors of childhood cancer [4]. For the convenience of the readership of Pediatric Cardiology, we add that recently our group published normal S 0 values with z-scores for healthy pediatric patients [3].…”
Section: To the Editorsupporting
confidence: 85%
“…This comparison probably would have improved the statistical power of their analysis, although we must state that the normal values for this age group are close to adult normal values. The remarkable study from Kocabas et al [2] clearly supports the notion that the right ventricle is susceptible to anthracycline in pediatric cancer patients. We thank the investigators for addressing the need for careful and systematic evaluation of both RV and LV function in the context of the need of cancer treatment with anthracycline in children and look forward for more interesting studies from this group.…”
Section: To the Editormentioning
confidence: 78%
See 2 more Smart Citations
“…16 The other study included 72 survivors and documented lower RV s ′ in the group treated with .240 mg/m 2 , but also lower RV myocardial performance index in survivors treated with lower anthracycline doses. 17 In addition, one study of 56 survivors of childhood cancer treated with anthracycline doses ,300 mg/m 2 found lower peak systolic strain values in the basal RV free wall, but not in the mid or apical free wall, and TAPSE was equal in patients and controls. 18 All the mentioned studies were on paediatric patients.…”
Section: Discussionmentioning
confidence: 99%